The Early Modern Zagori of Northwest Greece : An Interdisciplinary Archaeological Inquiry into a Montane Cultural Landscape. - Moudopoulos-Athanasiou, Faidon (Sidestone Press, 2022)
Landscape-archaeology projects have had a significant impact on our understanding of the deep history of the Greek countryside, but have overwhelmingly been limited to the plains and have rarely placed the Ottoman period at their core. This investigation of Zagori in Northwest Greece explores the archaeology and cultural history of a mountainous area that famously thrived in the Ottoman period. This engagement with an upland region in the early modern period s.